Effect of a controlled-release chlorhexidine chip on clinical and microbiological parameters and prostaglandin E2 levels in gingival crevicular fluid - Mizrak, Tansel; Guncu, Guliz N.; Caglayan, Feriha; Balci, Tansel Ansal; Aktar, Gulseren Samanci; Ipek, Fikret (Wiley, 2006)
Background: The aim of the present study was to determine the effect of a chlorhexidine chip on crevicular prostaglandin E-2 (PGE(2)) levels and on the clinical and microbiological parameters of periodontitis when used as adjunctive therapy to scaling and root planing (SRP) in patients with chronic periodontitis. Methods: This randomized single-blind study was carried out in parallel design. The test group received SRP plus chlorhexidine chip, whereas the control group received SRP alone. Thirty-four subjects, aged 20 to 55 years, with chronic periodontitis were recruited. Clinical indices, microbiological samples, and gingival crevicular fluid (GCF) samples were evaluated at baseline and after 1, 3, and 6 months. Microbiological samples were evaluated under a light microscope. GCF PG2 levels were determined using radioimmunoassay. Results: Significant improvements could be found for all clinical variables in both groups over the study period. The mean changes in probing depth obtained by SRP plus chlorhexidine chip were greater than those obtained by the SRP alone group at 3 and 6 months. In the test group, there was also significant gain in clinical attachment level at 6 months. When data were combined from all groups, significant reductions in GCF PGE(2) levels and number of microorganisms were noted at all time points. However, in the test group, reduction was greater at 6 months for crevicular PGE(2) level and at 3 and 6 months for proportions of spirochetes. Conclusion: Based on the findings of this study, the chlorhexidine chip reduced GCF PGE(2) levels and had positive effects on clinical parameters and subgingival flora when used as adjunctive therapy to SRP in patients with chronic periodontitis.
Keywords: chlorhexidine/therapeutic use; drug delivery systems; gingival crevicular fluid/analysis; prostaglandin E